The Effect of Combining Coffee Grounds Charcoal on The Quality of Rice Husk Briquettes With Varying Amounts of Molasses Adhesive - Mochammad Agung Indra Iswara; Susanto Susanto; Sigit Hadiantoro (Universitas Muhammadiyah Purwokerto, 2026)
Energy demands are increasing although fossil fuel resources are decreasing. Charcoal briquettes are used as an alternative renewable energy source, producing heat from biomass derived from agricultural waste. This study is aimed at a) determine the composition ratio of a waste combination including coffee grounds and rice husk charcoal as a carbon source, and b) evaluate the amount of molasses applied as an adhesive in briquette production to yield briquettes of optimal quality. The briquette production process consists of three stages: the preparation of materials by drying, followed by carbonization, then briquetting, and finally, the analytical testing of the resulting briquette products. The best briquettes produced in accordance with SNI standards from this study contain 3% adhesive, comprising 40 grams of coffee grounds charcoal and 60 grams of rice husk charcoal, with an ash content of 0.18%, a moisture content of 5%, a density of 0.97 g/cm³, and a calorific value of 5335.80 Cal/gram.